2000
DOI: 10.1159/000012077
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Clinical Significance of Lymph Node Micrometastasis Determined by Reverse Transcription-Polymerase Chain Reaction in Patients with Esophageal Carcinoma

Abstract: We investigated micrometastasis in lymph nodes by detecting carcinoembryonic antigen (CEA) mRNA. A total of 400 lymph nodes obtained from 21 patients with esophageal carcinoma were examined by CEA-specific reverse transcription-polymerase chain reaction (RT-PCR). Serial sections of positive lymph nodes were reexamined histologically and immunohistologically. Twenty-seven lymph nodes of 11 patients were diagnosed as being positive by conventional histologic examination. CEA-mRNA positivity was found in 18 of 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 21 publications
(22 reference statements)
0
33
1
Order By: Relevance
“…CEA is a most commonly used tumor marker for gastrointestinal cancers. Recent studies showed that CEAmRNA RT-PCR or CEA immunostaining is frequently used in detection of micrometastases of gastrointestinal tract cancers [1,12,28,29] . CEA levels in serum play an important role in monitoring patients with gastrointestinal cancer [30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEA is a most commonly used tumor marker for gastrointestinal cancers. Recent studies showed that CEAmRNA RT-PCR or CEA immunostaining is frequently used in detection of micrometastases of gastrointestinal tract cancers [1,12,28,29] . CEA levels in serum play an important role in monitoring patients with gastrointestinal cancer [30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…KL-1 reacts with cytokeratins (CK), components of intracytoplasmic network of intermediate filaments (Ifs) [4,8,35] , specifically reacts with epithelial tumors. Anti-CK mABs using immunocytochemistry or CK RT-PCR have been widely used for the detection of micrometastases in lymph nodes, venous blood and bone marrow [1,4,12,28,[36][37][38][39][40][41][42] . It is satisfactory using KL-1 monoclonal antibody to detect micrometastasis in the lungs and livers of the mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse transcription-PCR (RT-PCR) assay has been used frequently in recent years for the detection of occult cancer cells or micrometastasis in lymph nodes, bone marrow, and the peritoneal cavity (11)(12)(13)(14)(15). There have been several studies on the molecular detection of circulating cancer cells in the blood by RT-PCR targeted to carcinoembryonic antigen [CEA (16 -18)].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in an attempt to improve the sensitivity of histology in identifying lymph node metastasis, various techniques have been studied, including immunocytochemical analysis, with antibodies elicited towards cancer-specific antigenic determinants, and the molecular detection of cancer cells [2, 6, 7, 8, 9, 10, 11]. The latter approach has received particular attention not only in the identification of lymph node cancer cells, but also in their identification in blood and bone marrow [8, 9, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24]: it is highly sensitive, and therefore has great potential in identifying scarce cancer cells (1 cell in a population of 10 7 –10 8 ) [25].…”
Section: Introductionmentioning
confidence: 99%